The Determinants of Audit Quality: Audit Tenure, Audit Committee, and Audit Capacity Stress - Sudarmadi , Sudarmadi; Lasmana, Sadam (Goodwood Akuntansi dan Auditing Reviu, 2026)
Purpose: This study examines the effect of auditor tenure, audit committee composition, and audit capacity stress on audit quality in food and beverage manufacturing firms listed on the Indonesia Stock Exchange (IDX) during 2019–2023. Methodology/approach: A quantitative associative approach was applied using secondary data from the IDX. The sample consisted of 29 companies over five years (145 observations), selected through purposive sampling. Panel data regression analysis was conducted using EViews 12. Results: The results show that auditor tenure, audit committee, and audit capacity stress do not have a significant partial effect on audit quality. However, simultaneously, these variables significantly influence audit quality. Conclusions: Individually, the variables do not determine audit effectiveness, but collectively they influence audit outcomes. This indicates that audit quality depends on the interaction of multiple factors. Firms and regulators should emphasize auditor competence, independence, and workload management. Limitations: This study focuses only on manufacturing firms, particularly the food and beverage subsector, limiting generalizability to other industries. Contributions: This study provides insights for public accounting firms and regulators in improving audit quality and understanding its determinants in the manufacturing sector.